Diferenças microbiológicas entre úlceras falcêmicas e não falcêmicas - Aragão, Matheus Todt (2015)
INTRODUCTION: The ulcers of the lower limbs are cited as the main cutaneous manifestation of sickle-cell anemia. Infection of sickle-cell leg ulcers is often considered inevitable, but its role in the emergence and perpetuation of the injury remains controversial. This study aims to characterize the microbiota of leg ulcers in patients with sickle-cell anemia and compare it to the microbiota of ulcers of other etiologies. METHODS: This was a descriptive cross-sectional study, consisting of two groups (patients with sickle-cell leg ulcers and patients with ulcers of other etiologies), where was studied the lesion microbiota and its antimicrobial susceptibility. The material was collected with aseptic technique, by curettage of the ulcer, and was analyzed by standard and automated methods. RESULTS: Each group consisted of 19 patients, and was observed in patients with sickle-cell leg ulcer the prevalence of only one bacteria (57.9%), with 31.6% of sterile cultures, and Staphylococcus aureus (31.6 %) and Pseudomonas aeruginosa (26.3%) were the major microorganisms isolates. In the evaluation of antimicrobial resistance were observed 2 cases (40%) of P. aeruginosa resistant to aminoglycosides, 1 case (20%) to Ciprofloxacin and 3 cases (60%) to Cefepime, and 2 cases (33.3%) of S. aureus resistant to Oxacillin and 1 case (16.7%) to Linezolid. On ulcers of other etiologies were seen bacterial growth in 100% of the 19 cases, with higher microbial diversity and predominance of Gram-negative (89.5%), especially of Pseudomonas spp., Klebsiella spp. and Proteus mirabilis. The antibiogram demonstrated greater resistance, with evidence of resistance to fourth generation´s cephalosporins, carbapenems and aminoglycosides. In contrast, the lesions not related to sickle-cell disease showed more frequent bacterial isolation, higher microbial diversity and less favorable antimicrobial resistance profile. The study results suggest a weak relationship between the local flora and the evolution of sickle cell ulcers.